IDENTIFIKASI KEBISINGAN BERKENDARA MELEWATI KAWASAN PINGGIRAN HUTAN KOTA JEMBATAN MAHAKAM I DAN IV SAMARINDA DARI TAHUN 2016 S/D 2020 - Furqaan Hamsyani; Agustina Murniyati; Kiamah Fathirizki Aqsa Kamarati (Politeknik Pertanian Negeri Samarinda, 2023)
The urban forest is a community of vegetation in the form of trees and their associations that grow on city land or its surroundings. Air pollution that occurs in the urban forest reduces air quality so that its quality decreases to become unusable as it should be. The purpose of this study is to measure and identify driving noise and compare with environmental quality standards. The procedure of this research different density of vegetation from 2016-2020 has passed the Quality Standard, based on the criteria of Keputusan includes the stages of activity, namely field orientation to determine the point of Mahakam City Forest road length is 143 m, noise sampling points as many as 3 points with a distance per point is 71.5 m. The results of this study indicate that the number of vehicles passing by, the density of vegetation in the Mahakam Bridge City Forest is a factor in reducing the intensity of noise, where each measurement point has a Menteri Negara Lingkungan Hidup Nomor 48/MENLH/11/1996 tentang Baku Tingkat Kebisingan.